2010
DOI: 10.5038/2375-0901.13.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Safety and City Public Transport System: Case Study of Bengaluru, India

Abstract: Vehicle crashes are a major concern in rapidly growing urban agglomerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The bus body specifications are also a cause of concern when it comes to ensuring safety. Research has shown that low floor buses with maximum height of 550 cm from ground can help to reduce injury severity, especially in crashes involving a pedestrian being run over by a bus (Kharola et al, 2010). Such standards must be established at the national level to direct ve-hicle manufacturing and at the state and municipal levels to direct the purchasing of standard buses.…”
Section: Discussionmentioning
confidence: 99%
“…The bus body specifications are also a cause of concern when it comes to ensuring safety. Research has shown that low floor buses with maximum height of 550 cm from ground can help to reduce injury severity, especially in crashes involving a pedestrian being run over by a bus (Kharola et al, 2010). Such standards must be established at the national level to direct ve-hicle manufacturing and at the state and municipal levels to direct the purchasing of standard buses.…”
Section: Discussionmentioning
confidence: 99%
“…Due to absence of automatic doors, passengers are injured from a fall during boarding or alighting. Due to high ground clearance of bus, in case of a crash, pedestrians and cyclists are crushed under the wheels of buses, which would be prevented with a low clearance ( Kharola et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Travel happens when the end result creates a higher value that the costs (including monetary and time spent). It is evident, that commuting to work and school is an everyday activity that carries this value (Kharola et al, 2010). Despite that, traffic-related accidents are one of the top leading causes of death in the EU and in Hungary.…”
Section: Introductionmentioning
confidence: 99%